Positive Solutions for Coupled Nonlinear Fractional Differential Equations - Wenning Liu; Xingjie Yan; Wei Qi (Journal of Applied Mathematics)
We consider the existence of positive solutions for a coupled system of nonlinear fractional differential equations with integral boundary values. Assume the nonlinear term is superlinear in one equation and sublinear in the other equation. By constructing two cones K1, K2 and computing the fixed point index in product cone K1×K2, we obtain that the system has a pair of positive solutions. It is remarkable that it is established on the Cartesian product of two cones, in which the feature of two equations can be opposite.